169 Individual Differences in Postoperative Recovery Trajectories for Adult Symptomatic Lumbar Scoliosis. (1st April 2022) - Greenberg, Jacob K.; Bridwell, Keith; Landman, Joshua; Bess, Shay; Smith, Justin S.; Lenke, Lawrence; Shaffrey, Christopher I.; Kelly, Michael
Abstract : INTRODUCTION: The Adult Symptomatic Lumbar Scoliosis-1 (ASLS-1) trial demonstrated the overall benefit of ASLS surgery. However, the extent to which individuals differ in their postoperative recovery trajectories is unknown. METHODS: We included adult patients that underwent surgical treatment as part of the ASLS-1 study. We used multilevel models to analyze postoperative recovery trajectories in Oswestry Disability Index (ODI) and Scoliosis Research Society-22 (SRS-22) sub-scores, which were measured every three months until two years after surgery. The impact of baseline disability was measured using the conditional R2, which measured the variance explained by allowing each patient to have their own intercept (i.e., baseline disability). In addition, we created multilevel, multivariable models that identified the most influential trajectory moderators, including radiographic, comorbidity, pain/function, demographic, and surgical factors. The performance of these models was quantified using the marginal R2, which represented the amount of variability in ODI/SRS-22 collectively explained by each model. RESULTS: Among 178 included patients, there was substantial variability in recovery trajectories. Applying the average trajectory to each patient explained 15% of the variability in ODI and 21% of the variability in SRS sub-scores. However, accounting for differences in baseline disability levels explained an additional 56-57% of the variability in recovery trajectories. The final model predicting recovery trajectory for ODI explained 50% of the variability in recovery trajectories. The final model for SRS-22 explained 57% of the variability in recovery trajectories. CONCLUSION: ASLS patients have highly variable postoperative recovery trajectories, largely related to differences in baseline disability but also impacted by moderators such as number of levels fused.